1998
DOI: 10.1142/s0218127498000796
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Self-Organization of Bacterial Population

Abstract: The peculiarities of self-organization of a bacterial population are analyzed. Comparison of the dynamic characteristics of a bacterial population received experimentally by biological and optical methods is made. It is shown that the observable dynamic properties of population are connected with its spatial self-organization. Such behavior of moving microorganisms is a consequence of the search for optimum conditions of viability retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The appearance of advection-driven heterogeneity in relation to single and multispecies ecological interactions was studied by Levin (1977), Levin and Segel (1976), Okubo (1980), Mimura and Murray (1978), Mimura and Kawasaki (1980), Mimura and Yamaguti (1982) and many other authors. These studies form a theoretical basis for modelling complex spatio-temporal dynamics observed in real systems (e.g., Badaev et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of advection-driven heterogeneity in relation to single and multispecies ecological interactions was studied by Levin (1977), Levin and Segel (1976), Okubo (1980), Mimura and Murray (1978), Mimura and Kawasaki (1980), Mimura and Yamaguti (1982) and many other authors. These studies form a theoretical basis for modelling complex spatio-temporal dynamics observed in real systems (e.g., Badaev et al 1998).…”
Section: Introductionmentioning
confidence: 99%